Indian monsoon's relation with the decadal part of PDO in observations and NCAR CCSM4. (13th July 2016) - Krishnamurthy, Lakshmi; Krishnamurthy, V.
ABSTRACT: This study has investigated the influence of the decadal component of the Pacific Decadal Oscillation (PDO) on the Indian monsoon in observations and coupled climate model. A major part of the conventionally defined PDO is shown to be dominated by interannual variability. By extracting the pure decadal part of the North Pacific variability, this study has shown that the Indian monsoon rainfall exhibits different relations with the conventionally defined PDO and the pure decadal component of the PDO. This result may have implications for decadal prediction of the monsoon. The analysis suggests that the warm (cold) phase of pure decadal variability of PDO is associated with deficit (excess) rainfall over the west central part of India. In contrast, the conventional warm (cold) PDO index is associated with deficit (excess) rainfall over most of India. The warm phase of the pure decadal PDO opposes the moisture flow beyond 20°N over the Indian monsoon region via the meridional winds extending from the North Pacific and leads to reduced rainfall over west central India. The Community Climate System Model version 4 of the National Center for Atmospheric Research shows reasonable simulation of the decadal PDO mode in both the North Pacific sea surface temperature and the Indian monsoon rainfall and the relation between them. Further, the observed and simulated PDO–monsoon relation is substantiated through a regionally de‐coupled experiment. The coupled model experiment also provides supporting evidence for the mechanism involving the intermediary role played by the tropical Pacific Ocean in the PDO–monsoon relation.